THE NEWLY DEVELOPED HIGHLY SENSITIVE METHOD FOR THE DETERMINATION OF CAPECITABINE BY USING UV-SPECTROSCOPY (International Journal of Pharmaceutical Sciences and Drug Research, 2019)
Capecitabine is a fluoropyrimidine carbamate, designed as 'pro-drug' to the cytotoxic agent 5-fluorouracil (5-FU) meant to be administered orally. Capecitabine is used as first line monotherapy for metastatic colorectal cancer. In the present study simple, rapid, accurate UV spectrophotometric methods were developed and validated for the estimation of capecitabine in bulk and its formulations as per ICH guidelines. Three solvent systems viz., 0.1N NaOH, 0.1N HCl and Methanol: Water (1:3) were tried. The results suggest that the developed methods shows linearity over the concentration range of 2-24μg/ml with a correlation coefficient of 0.9999. All the developed methods were statistically validated for accuracy, precision, linearity, robustness, and ruggedness as per ICH guidelines. The % RSD values for validated methods were found to be less than 1.5 and methods will find application in routine analysis of drug formulations containing capecitabine.